Unregistered Polygamy Validation: Isbat Nikah, Polygamy Permit, and Due Process of Law in Indonesian Religious Courts - Alfitri, Alfitri; Imanullah, Rijal; Rahman, Aulia (Ulumuna, 2024)
This article probes whether methods of validating unregistered polygamy in Indonesian Religious Courts have honored the due process of law. Judges have adopted two different methods in validating unregistered polygamy: first, by ordering concerned parties to apply for the issuance of a retroactive marriage certificate (isbat nikah), and second, by advising them to submit a polygamy permit application. Using the sociolegal approach in examining Ratio Legis and selected cases on unregistered polygamy validation across Indonesia, it finds that the existing methods have impacted protecting women’s and children’s rights and marriage law objectives. Opting for isbat nikah means perpetuating violations of the marriage law provisions and objectives, which restrict polygamy through court proceedings to be orderly administration and protect women’s and children’s rights. Meanwhile, requiring unregistered polygamists to remarry by applying for a polygamy permit could impact wives’ rights who are married without registration and their children’s. The 2018 Supreme Court’s Circular prohibiting the Religious Court from accepting applications for isbat nikah of unregistered polygamy shows its tendency to the formal application of the marriage law provisions. Even so, judges adopt the contentious isbat nikah to legalize unregistered polygamy, mainly when the parties involved accept their polygamy and live peacefully. This bottom-up approach arguably better meets the principles of fairness because all legal rights owed to concerned parties are respected.